The Effect Of The #AwasModus Campaign At @bankbca Tiktok On Community Financial Literacy - Michael; Susilo, Daniel (Airlangga University, 2023)
In Indonesia, the increase in the level of financial inclusion and literacy in the community is not balanced. There is a considerable gap between the high level of financial inclusion and low financial literacy, which opens a gap of opportunity for bank fraud mode behavior to carry out its actions. The perpetrators of the fraud mode, on behalf of the bank irresponsibly. Bank BCA, which is also one of the banks that experienced this phenomenon, conducted a campaign that became one of the preventive measures to deliver educational messages to the public as a form of financial literacy. The purpose of this research is to find out whether there is an influence between the #AwasModus campaign message delivered by BCA on the level of public financial literacy. The concepts used in the study used the concepts of campaign messages and financial literacy. The method used is explanatory quantitative using a questionnaire survey to 201 respondents. And the results of this study indicate that the independent variable, namely the campaign message, has an influence on the dependent variable, namely financial literacy, by 33.1%. The conclusion of this study is that there is an influence between the #AwasModus campaign message on Tiktok @bankbca on people's financial literacy.